The Foundation “Victimas del Terrorismo en España” (Victims of Terrorism in Spain) and the program “Educar para la convivencia” (Education for Peaceful Co-existence) - Blanco Garrido, María Mar (Trabajo Social UNAM, 2017)
In Spain there has existed and still exists an important threat from terrorists, a result of the actions of both national (ETA, GRAPO) and international organizations (Al Qaeda, ISIS, among others). The Victims of Terrorism Foundation came into being in 2001 to provide integral assistance to victims of terrorism and support and collaboration with various associations and foundations of victims. One of its most important activities is the program, Education for Peaceful Co-existence, which takes testimonials of victims to educational centers. The adolescents who take part in this project later take part in the School Awards, “A City Free of Violence.” The testimonials of victims in the classroom have been adopted as part of the new basic curriculum in Primary, Obligatory Secondary and High School education. These also include transversal elements such as rejection of terrorist violence, respect and consideration for the victims and prevention of terrorism. These same elements are present in the new basic curriculum of Professional Studies.